Postembolization fever after transarterial chemoembolization is a sign of unfavorable therapeutic response in hepatocellular carcinoma patients. Issue 2 (17th May 2020) - Peng, Chien‐Wei; Teng, Wei; Hsieh, Yi‐Chung; Jeng, Wen‐Juei; Huang, Chien‐Hao; Lui, Kar‐Wai; Hung, Chen‐Fu; Chen, Yi‐Cheng; Lin, Chen‐Chun; Lin, Chun‐Yen; Lin, Shi‐Ming; Sheen, I‐Shyan
Abstract: Transarterial chemoembolization (TACE) is the standard of care for intermediate‐stage hepatocellular carcinoma (HCC) patients. The postembolization fever (PEF) is observed in 20% to 73% patients. This study aims to investigate the predictive factors of PEF and its impact on therapeutic response. From 2010 to 2015, a total of 525 HCC treatment naïve patients treated by TACE were recruited. Age, gender, etiologies of HCC, cirrhosis, tumor status, and pretherapy liver biochemistry were compared between patients with and without PEF. Predictors of PEF, complete response (CR), and progressive disease were analyzed by logistic regression. The PEF was observed in 185 patients (35.2%). The beyond up‐to‐seven, AST >2X upper limit of normal (ULN) and ALBI grade ≧2 were the independent predictors of PEF. Patients with PEF were less likely to achieve CR (18.4% vs 32.1%, P = .0017). Patients whose tumor burden beyond "up‐to‐seven" criteria with presence of tumor fever are least likely to achieve CR (aOR: 0.08, P = .022) and had higher risk for disease progression (aOR: 2.13, P = .082). PEF is related to heavier tumor burden and poorer liver reserve function. The presence of PEF is an unfavorable phenomenon correlating with poorer treatment response.